Investigating the acceptance and use of Wikipedia as a major information source - Jiang, Tao (2010)
Wikipedia is the biggest multilingual free-content encyclopedia on the Internet. As of April 2008, there were more than 75,000 active contributors working on more than 10,000,000 articles in more than 250 languages, and still growing. Wikipedia became more and more popular with students. Thus it is necessary to investigating the use of it by the local students. This study investigated the factors influencing on the behavior intention and the use behavior to use Wikipedia as a major information source by the local university students. The research model was generated mainly based on the Unified Theory of Acceptance and Use of Technology (UATAUT), and some other previous widely accepted models. This study used the survey methodology. There were seventy-three students of a local university participating in the survey. The study found that the constructs from UTAUT (performance expectancy, effort expectancy, and social influence) were all significant to behavior intention. The other two constructs (attitude, and anxiety) from other previous models were significant to behavior intention. The use behavior was found determined by facilitating conditions and behavioral intention. This study may help the local university educators and the practitioner of Wikipedia to better understand how and why their students preferred to use Wikipedia as a major information source.